Insights into the mechanisms of microbiome and metabolome changes mediated by understory interplanting mode in Polygonatum sibiricum - Wang, Yue; Zhang, Jin; Sun, Jiabo; Li, Guoqing; Wang, Qian; Zhao, Yanxia; Ma, Changjian; Han, Jinlong (Frontiers in Microbiology, 2023)
Polygonatum sibiricum is an understory economic plant, and its dried rhizome is a traditional Chinese medicine. The purpose of this study was to connect the quality improvement of the understory plant P. sibiricum with specific microorganisms. Therefore, amplicon and metabolome sequencing were conducted for P. sibiricum interplanted under three types of trees and in the field, and the relationship between the microbiome and secondary metabolism was explored. Principal component analysis (PCA) divided field cultivated and understory interplanted groups into two classes. A total of 95 different metabolites were found, with four expression patterns. The alpha diversity of rhizosphere bacteria and endosphere fungi in the understory interplanted group was significantly higher than that in the farmland cultivated group. There were 276 different rhizosphere microorganism genera among the four groups; however, only 33 different endosphere genera were observed, indicating that endophytic microbial diversity was relatively stable within the P. sibiricum rhizome, especially for endosphere bacteria. Cointertia analysis (CoIA) suggested that the metabolite changes in P. sibiricum induced by interplanting under different trees were more strongly affected by rhizosphere microorganisms than by endosphere microorganisms. In addition, the interactions between rhizosphere microorganisms and metabolites in the farmland group were weakened compared with those in the underplanted groups. Canonical correspondence analysis (CCA) showed that Aspergillus and Ellin6067 had the greatest influence on the metabolites.